The effects of sustained COVID‐19 emergency and restrictions on the mental health of subjects with serious mental illness: A prospective study - Barone, Annarita; Billeci, Martina; D'Amore, Sofia; De Prisco, Michele; De Simone, Giuseppe; Ermini, Eleonora; Freda, Vittorio; Iannotta, Federica; Luciani, Adalgisa; Pistone, Luca; Rifici, Lorenza M.; Saia, Viviana M.; et al. (Journal of community psychology, 2023)
Few longitudinal studies have so far investigated the impact of sustained COVID‐19 among people with pre‐existing psychiatric disorders. We conducted a prospective study involving people with serious mental illness (n = 114) and healthy controls (n = 41) to assess changes in the Perceived Stress Scale, Generalized Anxiety Disorder Scale, Patient Health Questionnaire, and Specific Psychotic Experiences Questionnaire scores 18 months after the COVID‐19 pandemic outset. Subjects underwent interviews with a mental health professional in April 2020 and at the end of the local third wave (October 2021). A significant increase in perceived stress was found in healthy controls, especially females. Psychiatric patients showed a significant worsening of anxiety symptoms compared to baseline records (t = −2.3, p = 0.036). Patients who rejected vaccination had significantly higher paranoia scores compared to those willing to get vaccinated (U = 649.5, z = −2.02, p = 0.04). These findings indicate that COVID‐19's sustained emergency may cause enduring consequences on mental health, soliciting further investigations.